ESTIMATION OF VARIABILITY-CORRELATION AND PATH COEFFICIENT ANALYSIS FOR YIELD AND YIELD COMPONENTS OF FABA BEAN GENOTYPES - Zibari, Payman A. A.; Teli, Zhiyan A.; Hussain, Mohammed A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Four genotypes of faba bean Vicia faba L. (Aknadcge, FlIP-17-078FB, FLIP-17-072FB and Fiedo were carried out during 2020-2021 winter season in year under four levels of phosphorus (0.0 18,36 and 54 Kg ha-1) at the farm of field crops department, college of Agricultural Engineering science, University of Duhok, the experiment unit ranged in factorial within randomized complete block design with three replications. The result show significant effect of faba bean genotypes for all studies traits except plant height and main branches per plant and number of seed per plant, while the phosphorus level exhibited highly significant effect on all studies traits except plant Height and main branches the interaction between genotypes and phosphorus levels show significant effect for days to flowering, pod length, 100 seed weight and number nodes per plant and the rest traits exhibited non-significant. The fedo genotypes was superior in pod weight, 100 seed weight, number of nodules plant-1 and number of pods plant-1. The seed yield gave positive correlation with number of nodules plant-1 (0.742, 0.751) phenotypic and genotypic and positive correlation with 100 seed weight (0.673 and 0.694).